Cardiovascular Disease Risk is Only Elevated in Hypertensive, Formerly Preeclamptic Women. Issue 2 (June 2016) - Breetveld, N.M.; Ghossein-Doha, C.; van Kuijk, S.; van Dijk, A.P.; van der Vlugt, M.J.; Heidema, W.M.; Scholten, R.R.; Spaanderman, M.E.
Abstract : ( BJOG. 2015;122(8):1092–1100) Preeclampsia (PE) complicates 5% to 8% of all pregnancies and is associated with an increased risk for premature cardiovascular disease (CVD) later in life. Patients with a history of PE have a 2-fold to 7-fold risk of developing ischemic cardiac disease compared with healthy controls, depending on gestational age at delivery, and about a 4-fold risk of developing chronic hypertension within 15 years after pregnancy. Although it is unknown whether PE itself increases the risk of CVD independently or through risk factors associated with both PE and CVD, patients with a history of PE tend to exhibit components of the metabolic syndrome compared with patients with a history of uncomplicated pregnancy. Quantifying person-specific CVD risk could be useful in counseling these patients.